An Analysis of a Mobile Vehicle with Dual Run - Hlavna, Vladimir; Fitz, Pavel; Istenik, Rastislav (Communications - Scientific Letters of the University of Zilina, 2001)
Plane motion of a model vehicle with additional equipment is theoretically solved in this paper. The paper further deals with some questions concerning spatial motion of a dual-run wheel and consequences of such motion. The used method allows changing an arbitrary parameter in a very simple and effective way. The objective of the paper is to compare velocity, mass, stiffness and impact of damping on the vehicle motion. A test stand to measure properties of wheel-track-ground interactions was also designed.
Keywords: no keywords